A Field Study of Scale Economies in Software Maintenance - Banker, Rajiv D.; Slaughter, Sandra A. (Management Science, 1997)
Software maintenance is a major concern for organizations. Productivity gains in software maintenance can enable redeployment of Information Systems resources to other activities. Thus, it is important to understand how software maintenance productivity can be improved. In this study, we investigate the relationship between project size and software maintenance productivity. We explore scale economies in software maintenance by examining a number of software enhancement projects at a large financial services organization. We use Data Envelopment Analysis (DEA) to estimate the functional relationship between maintenance inputs and outputs and employ DEA-based statistical tests to evaluate returns to scale for the projects. Our results indicate the presence of significant scale economies in software maintenance, and are robust to a number of sensitivity checks. For our sample of projects, there is the potential to reduce software maintenance costs 36% by batching smaller modification projects into larger planned releases. We conclude by rationalizing why the software managers at our research site do not take advantage of scale economies in software maintenance. Our analysis considers the opportunity costs of delaying projects to batch them into larger size projects as a potential explanation for the managers' behavior.